Kompetensi Petani Dalam Usahatani Talas Beneng di Kabupaten Majalengka - Meinata Bella Ayutianti; Sapja Anantanyu; Eksa Rusdiyana (Universitas Sebelas Maret, 2026)
The agricultural sector in Indonesia plays a very large role in supporting Indonesia's economic development. Majalengka Regency is one of the producers of beneng taro plants. The low productivity results indicate that the competence of beneng taro farmers in their farms is not optimal. The research objectives (1) examine the level of competence of farmers in conducting beneng taro farming in Majalengka Regency, (2) examine the factors of age, formal education, non-formal education, beneng taro farming experience, cosmopolitan level, land area, the role of agricultural extension agents, community roles, outside network support, (3) examine the influence of age, formal education, non-formal education, beneng taro farming experience, cosmopolitan level, land area, the role of agricultural extension agents, community roles, outside network support. This research uses quantitative methods of data collection using questionnaires, research conducted in Majalengka Regency. The research population was farmer groups who were cultivating beneng taro. Determination of representative samples obtained the results of 90 samples. Data analysis using multiple linear regression analysis with the IBM SPSS Statistic 25 application.The results of the study; (1) The level of competence of farmers is mostly in the medium category. (2) Factors that influence the level of competence of farmers in beneng taro farming in Majalengka Regency, late adult age, formal education at the junior high school / equivalent level, very low non-formal education, farming experience of 5-6 years, the level of cosmopolitan farmers is rare, the land area is high, and the role of extension workers, the role of the community, the support of outside networks. (3) The test results of significant influence are age, formal education, non-formal education, farming experience, land area, community roles and external networks. Cosmopolitan level and the role of extension workers do not have a significant effect. Simultaneously / overall variables on the competence of farmers in taro farming beneng significant effect.